Air-conditioning equipment at Fertilizer Machinery Laboratory (1935)
General view of the air-conditioning equipment used in the U.S. Department of Agriculture's Fertilizer Machinery Laboratory located at the Arlington Experimental Farm in Rosslyn [Arlington], Virginia. This particular equipment was used to control temperature and relative humidity in the laboratory's fertilizer distributor testing room. Established by an act of Congress in April 1900, Arlington Farm served as the main field laboratory for the Bureau of Soils, U.S. Department of Agriculture, until 1941.
Keywords: Nitrogen fertilizer industry; United States. Bureau of Chemistry and Soils; Air conditioning; United States. Department of Agriculture; Machinery